2020
DOI: 10.1021/acs.est.9b07497
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Monoterpene-Derived α-Hydroxyalkyl-Hydroperoxides in Aqueous Organic Media: Relevance to the Fate of Hydroperoxides in Aerosol Particle Phases

Abstract: The -hydroxyalkyl-hydroperoxides [R-(H)C(-OH)(-OOH), -HH] produced in the ozonolysis of unsaturated organic compounds may contribute to SOA aging. -HHs inherent instability, however, hampers their detection and a positive assessment of their actual role. Here we report, for the first time, the rates and products of the decomposition of the -HHs generated in the ozonolysis of atmospherically important monoterpenes -pinene (-P), dlimonene (d-L), -terpinene (-Tn) and -terpineol (-Tp) in water:acetonitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(125 citation statements)
references
References 70 publications
11
114
0
Order By: Relevance
“…Solute strength may change the pH dependence of γ SO 2 in two ways. First, the solubility of SO 2 may decrease and become less dependent on pH as ionic strength increases (Rodríguez-Sevilla et al, 2002). A former study (Leng et al, 2015) has shown that the effective Henry's law of triethylamine decreases with increased ionic strength.…”
Section: So 2 Uptake and Aerosol Phmentioning
confidence: 99%
“…Solute strength may change the pH dependence of γ SO 2 in two ways. First, the solubility of SO 2 may decrease and become less dependent on pH as ionic strength increases (Rodríguez-Sevilla et al, 2002). A former study (Leng et al, 2015) has shown that the effective Henry's law of triethylamine decreases with increased ionic strength.…”
Section: So 2 Uptake and Aerosol Phmentioning
confidence: 99%
“…The mean RF of  OH, ordered from lowest to highest are: 21% (Hyytiälä) < 38% (Mainz) < 53% (Beijing). The presence of  OH is related to multiple formation pathways, such as Fenton-like reactions, thermal or hydrolytic decomposition of peroxide-containing HOMs, and redox chemistry of environmentally persistent free radicals or aromatic compounds-containing humic-like substances (Chevallier et al, 2004;Valavanidis et al, 2005;Li et al, 2008;Page et al, 2012;Gehling et al, 2014;Tong et al, 2016a;Tong et al, 2017;Tong et al, 2018;Tong et al, 2019;Qiu et al, 2020). The mean RF of O2 only varies slightly in the range of 2-6%, showing no clear trend and within the range of standard errors in 3.2 Mass-specific and air sample volume-specific yields of RS from ambient PM2.5 Figure 3 shows the mass-specific and air sample volume-specific yields of reactive species (RS) including radicals, H2O2, and the sum of radicals and H2O2 by PM2.5 from Hyytiälä, Mainz, and Beijing.…”
Section: Determination Of Water-soluble Transition Metal Concentrationsmentioning
confidence: 99%
“…(HOMs) (Chen et al, 2010;Wang et al, 2011b;Tong et al, 2016a;Tong et al, 2018;Tong et al, 2019;Fang et al, 2020;Qiu et al, 2020). Moreover, the humic-like substances and other multifunctional compounds containing carboxyl, carboxylate, phenolic, and quinoid groups may influence the redox activity of PM via chelating transition metals (Laglera and van den Berg, 2009;Kostić et al, 2011;Catrouillet et al, 2014;Gonzalez et al, 2017;Wang et al, 2018c;Win et al, 2018;Wei et al, 2019).…”
mentioning
confidence: 99%
“…Organic peroxides generated from both biogenic and anthropogenic hydrocarbon emissions are abundant in submicron aerosol. Given that they are highly reactive with relatively short lifetimes (Bonn et al, 2004;Krapf et al, 2016;Qiu et al, 2020), these species could serve as important condensed phase oxidants for gas phase SO2. Combining laboratory measurements and model predictions, the current study investigated heterogeneous reactions between SO2 and particulate organic peroxide.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%